2017
DOI: 10.1016/j.ejpb.2016.12.021
|View full text |Cite
|
Sign up to set email alerts
|

New scaffolds encapsulating TGF-β3/BMP-7 combinations driving strong chondrogenic differentiation

Abstract: Funding:Highlights:• The sustained delivery of BMP-7 enhances the chondrogenic activity of TGF-β3.• BMP-7 and TGF-β3 can be entrapped in polymers matrices as PEG-heparin complexes.• Scaffolds delivering TGF-β3 and BMP-7 drive the chondrogenesis of cell progenitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…Soluble factors individually and synergistically supported chondrocytes/stem cells toward chondrogenesis in both monolayer and pellet culture [91,99,200,208,209]. Supplementation with soluble factors, such as TGF-β, BMP and Mechano Growth Factor (MGF) IGF-I, into various scaffolds promoted efficient cartilage formation in human MSCs [210,211], indicating that these soluble factors could enhance chondrogenesis. Furthermore, it has been reported that TGF-β could bind to heparin sulfate [212] while GAGs stimulated the release of free and bioactive IGF-I in vitro [213], indicating that the interaction of soluble factors and GAGs may potentially influence chondrogenic differentiation.…”
Section: Chemical Componentsmentioning
confidence: 99%
“…Soluble factors individually and synergistically supported chondrocytes/stem cells toward chondrogenesis in both monolayer and pellet culture [91,99,200,208,209]. Supplementation with soluble factors, such as TGF-β, BMP and Mechano Growth Factor (MGF) IGF-I, into various scaffolds promoted efficient cartilage formation in human MSCs [210,211], indicating that these soluble factors could enhance chondrogenesis. Furthermore, it has been reported that TGF-β could bind to heparin sulfate [212] while GAGs stimulated the release of free and bioactive IGF-I in vitro [213], indicating that the interaction of soluble factors and GAGs may potentially influence chondrogenic differentiation.…”
Section: Chemical Componentsmentioning
confidence: 99%
“…Stimulating factors are necessary for cartilage engineering and responsible for inducing, accelerating, and/or enhancing cartilage formation. Common stimulating factors include BMP-2/-4, insulin-like growth factor (IGF)-1, and TGF-β1/-β3 [76,77,78]. Moreover, physical stimuli, such as hydrostatic pressure and dynamic compression, have been explored to induce MSC-mediated cartilage formation [79].…”
Section: Msc-based Regenerative Medicinementioning
confidence: 99%
“…133 PLGA scaffold with BMP-7/TGF-B3 nanocomplexesin vitro human MSCsControlled supplementation of BMP-7 can improve the chondrogenic effect of TGF-β3, and scaffolds loaded with this combination of growth factors can induce cartilage formation in hMSC culturesRef. 134 FGF-18 (Sprifermin)Intraarticular injectionHuman kneeqMRI showed increased cartilage thickness in a dose-dependent manner in knee OA patients with acceptable safety profile at 3 yearsRef. 135 Collagen membrane (Chondrogide)Sheep cartilage defectPotentiated the healing of a microfracture treated cartilage defect with improved weight bearing, O’Driscoll sore, and Type II collagen stainingRef.…”
Section: Advances In Cartilage Tissue Engineering and Regenerative Thmentioning
confidence: 99%